TINDAK EKSPRESIF PUJIAN DALAM BAHASA BANJAR [Expressive Speech Acts Compliment the Banjar Language] - Rissari Yayuk (Kantor Bahasa Provinsi Maluku, 2016)
This research material in expressive speech acts compliment the Banjar people. The problem studied 1) How is the follow-expressive form of compliment in Banjar, 2) What sentence mode used in compliment speech acts expressive e,3) what politeness strategies used in the follow-expressive of Banjar language. The purpose of research included the description of 1) the form of the expressive act of compliment in Banjar, 2) sentence mode used in speech acts expressive of compliment,3) politeness strategies used in the follow-expressive Banjar language.. The method used descriptive qualitative. Research techniques were recorded and noted. Source data from Martapura city on June 2015 until January 2016 .the research found that the expressive act of compliment in Banjar language was characterized by umay'amboi modalities ', salut'salut', and the dasar of 'dasar'. This speech spoken in an enjoy situation . In generally utterances have news or declarative sentence mode. Flat intonation of sentences accompanied by a friendly smile of speakers. The use of this complimentacts of adhering to the principles of politeness (maxim) modesty. Humility is characterized by emphasizing the compliment of others advantages. Penelitian ini mengangkat materi tindak tutur ekspresif pujian pada masyarakat Banjar. Masalah yang dikaji 1) Bagaimana wujud tindak ekspresif pujian dalam bahasa Banjar, 2) Modus kalimat apa yang digunakan dalam tindak tutur ekspresif pujian, 3) Strategi kesantunan apa yang digunakan dalam tindak ekspresif bahasa Banjar. Tujuan penelitian meliputi pendeskripsian 1) wujud tindak ekspresif pujian dalam bahasa Banjar, 2) Modus kalimat yang digunakan dalam tindak tutur ekspresif pujian, 3) Strategi kesantunan yang digunakan dalam tindak ekspresif bahasa Banjar. Metode yang digunakan deskritif kualitatif. Teknik penelitian adalah rekam dan catat. Sumber data dari kota Martapura . Waktu pengambilan data Juni 2015 sampai dengan Januari 2016 .Berdasarkan hasil penelitian ditemukan Wujud tindak ekspresif pujian dalam bahasa Banjar ini ditandai dengan modalitas umay’amboi’, salut’salut’, dan dasar’ dasar’. Ujaran ini dituturkan dalam situasi santai.Pada umumnya tuturan memiliki modus kalimat berita atau deklaratif. Intonasi kalimat datar dengan disertai senyum ramah penutur. Penggunaan tindak pujian ini berpegang kepada prinsip kesantunan (maksim) kerendahantian. Kerendahatian ditandai dengan mengutamakan pujian kepada kelebihan yang dimiliki orang lain.